2017
DOI: 10.1155/2017/4969765
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Accurate Prediction of Liquid Loading of Directional Gas Wells in Transition Flow or Turbulent Flow

Abstract: Current common models for calculating continuous liquid-carrying critical gas velocity are established based on vertical wells and laminar flow without considering the influence of deviation angle and Reynolds number on liquid-carrying. With the increase of the directional well in transition flow or turbulent flow, the current common models cannot accurately predict the critical gas velocity of these wells. So we built a new model to predict continuous liquid-carrying critical gas velocity for directional well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Wenming Yang et al 46 established a calculation model of gas critical liquid‐carrying flow rate with high gas‐liquid ratio in directional gas wells based on the relationship between well deviation angle, drag coefficient and Reynolds number. Ruiqing Ming et al 47 considered the influence of directional well inclination angle and Reynolds number on gas liquid carrying, and established a calculation model of gas critical liquid‐carrying flow rate for continuous liquid carrying in transitional and turbulent flow.…”
Section: Analysis Of the Current Situation Of Gas Critical Liquid Car...mentioning
confidence: 99%
See 2 more Smart Citations
“…Wenming Yang et al 46 established a calculation model of gas critical liquid‐carrying flow rate with high gas‐liquid ratio in directional gas wells based on the relationship between well deviation angle, drag coefficient and Reynolds number. Ruiqing Ming et al 47 considered the influence of directional well inclination angle and Reynolds number on gas liquid carrying, and established a calculation model of gas critical liquid‐carrying flow rate for continuous liquid carrying in transitional and turbulent flow.…”
Section: Analysis Of the Current Situation Of Gas Critical Liquid Car...mentioning
confidence: 99%
“…After adjusting coefficients, this model is widely used in liquid accumulation prediction at existing oil and gas well sites 5–7 . However, for gas wells with low pressure and low production, such as the Sulige Gas Field, the on‐site gas phase is mostly in a turbulent state, and the calculation using the Turner model has a large deviation 8,9 . In the low‐permeability water‐producing gas reservoir in the Daniudi gas field, widely used models such as the Turner model and the Min Li model have an average accuracy rate of predicting liquid accumulation in gas wells below 70% 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their model was reported to outperform both Turner and Belfroid models. Ming & He (2017) performed an experiment in deviated and horizontal wells. They reported that film will be formed in such wells and that the film will drop down in the tubing to initiate loading.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the gas reservoir depletes, the gas velocity decreases [1], the formation pressure attenuates, and the temperature decreases, so that the gas cannot carry the formation liquid out of the wellbore. This phenomenon is called liquid loading of gas wells [2][3][4]. Geng et al also pointed out that the discontinuity of gas is the fundamental cause of gas-well effusion [5], so it is easy to form effusion in the middle and late stage of gas-well production.…”
Section: Introductionmentioning
confidence: 99%